Pro Bash programming scripting the GNU/Linux shell - Johnson, Chris F. A. (Apress, 2009)
"The bash shell is a complete programming language, not merely a glue to combine external Linux commands. By taking full advantage of shell internals, shell programs can perform as snappily as utilities written in C or other compiled languages"--Resource description page
Print version record
Keywords: UNIX Shells; UNIX (Computer file); Operating systems (Computers); User interfaces (Computer systems); User-Computer Interface; Systèmes d'exploitation (Ordinateurs); Interfaces utilisateurs (Informatique); operating systems; COMPUTERS; Reference; COMPUTERS; Machine Theory; COMPUTERS; Computer Literacy; COMPUTERS; Information Technology; COMPUTERS; Data Processing; COMPUTERS; Computer Science; COMPUTERS; Hardware; General; Informatique